Comparison of thermal behaviour of different land cover types in Slovenia and Czech Republic - Miroslav Vysoudil; Karolina Kácovská; Darko Ogrin (Dela, 2021)
This paper presents the results of a study of thermal behaviour of different land cover types in the Czech Republic and Slovenia. A hand-held thermal camera, Fluke Ti55, was used for data collection. Variation in the values of the surface temperature characteristics reflects the geographically dissimilar spaces. The investigation demonstrated impact of dense green vegetation and water bodies on the balanced thermal behaviour of landscapes in both countries. Thus, they appear to be cold spots with the lowest values. The most obvious variation in surface temperature is associated with artificial areas and bare surfaces. They usually represent hot spots in the landscape. In both countries similar thermal behaviour was found in artificial land cover types as opposed to agricultural land cover types.